2015
DOI: 10.1007/s12032-015-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase II open-label clinical study of comparing nab-paclitaxel with pemetrexed as second-line chemotherapy for patients with stage IIIB/IV non-small-cell lung cancer

Abstract: Current choices of second-line chemotherapy regimens for patients with advanced non-small-cell lung cancer (NSCLC) are extremely limited. We applied a new strategy of using nab-paclitaxel as single chemotherapy regimen in second-line setting for patients with unsuccessful first-line chemotherapy. The efficacy and safety were compared with patients who received standard second-line regimen pemetrexed. Patients with stage IIIB/IV NSCLC and unsuccessful first-line platinum-based chemotherapy were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Patients in our study tolerated nab -paclitaxel well as salvage therapy, consistent with other reports showing a favorable toxicity profile for the drug as a single agent[8, 14-16, 25]. A phase I/II trial by Rizvi et al of nab -paclitaxel given weekly at 125mg/m 2 for the front-line treatment of advanced NSCLC reported neutropenia, leukopenia, sensory neuropathy, and fatigue as the most common grade 3/4 toxicities[10].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Patients in our study tolerated nab -paclitaxel well as salvage therapy, consistent with other reports showing a favorable toxicity profile for the drug as a single agent[8, 14-16, 25]. A phase I/II trial by Rizvi et al of nab -paclitaxel given weekly at 125mg/m 2 for the front-line treatment of advanced NSCLC reported neutropenia, leukopenia, sensory neuropathy, and fatigue as the most common grade 3/4 toxicities[10].…”
Section: Discussionsupporting
confidence: 91%
“…The ORR in the nab-paclitaxel arm was 14.5% with a disease control rate of 65.5%. The median PFS was 5.1 months for nab-paclitaxel and 4.6 months for pemetrexed, with the difference not being statistically significant[16]. Together these data as well as those presented in our study provide evidence for the efficacy of nab -paclitaxel beyond front-line therapy in advanced NSCLC and suggest that Eastern and Western populations may respond similarly to the drug in this setting.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…on days 1, 8 and 15 of a 28-day cycle. Liu et al [19] compared the median PFS of patients with advanced NSCLC after unsuccessful first-line chemotherapy and the results showed that the nab -paclitaxel had better PFS (5.1 months) than pemetrexed (4.6 months). Similarly, our study also showed that the nab -paclitaxel had good efficacy in PFS (4.6 months).…”
Section: Discussionmentioning
confidence: 99%